A study on the effect of solcoseryl-dental adhesive paste on wound healing in mice - Pantua, Annie Grace P.
A lot of wound healing supplements are currently available in the market. These agents can promote healing and decrease the risk of complications and patient discomfort. The aim of this study is to test another product, Solcoseryl-Dental Adhesive Paste, and determine if the wounds treated with the product heals faster than the control not receiving any medication. A histologic evaluation was done based on the given criteria. Twenty-four 7- week old white mice were used in the study. Data was gathered 2, 5 and 7 days after mucosal incision. Results showed that there was no significant difference in any of the criteria assessed for wound healing between the control and experimental groups. It can be concluded that the effect of Solcoseryl-dental adhesive paste on mucosal incisions in mice is comparable to the control.